Personal resilience on romantic relationship dissolution among emerging young adults - Chan, Siaw Leng (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
Malaysia is alarmed by the increasing rate of attempted suicide and suicide cases, as well as psychiatric illnesses such as anxiety and depression. Adolescents and young adults aged from 15 to 34 have been reported as a high-risk group for suicide whereby the leading causes of their death were due to relationship problems, particularly boy-girl relationship. The current study was to measure the level scores for Resilience Scale (RS) among Malaysia’s emerging young adults. Five characteristics of RS were explored to examine which characteristic contributes to the highest level in relationship dissolutions. This study included 293 young adults (aged 18 to 29) from Klang Valley where 168 (57.3%) were females and 125 (42.7%) were males. The study used RS and demographic information items. This study indicated that emerging young adults were at the range of moderately-low to moderate level of resilience. The results also showed that characteristic of equanimity, existential-aloneness, and perseverance contributed the highest level among the five characteristics of RS followed by existential aloneness and perseverance. The findings of this study were essential to assist mental health professionals such as counselors, psychotherapists, psychologists, and social workers to explore the most accurate assessment as well as different intervention alternatives based on individuals’ characters such as personal resilience as tools in the process of helping for dealing with relationship dissolution issues.